2011
DOI: 10.1063/1.3587583
|View full text |Cite
|
Sign up to set email alerts
|

J∕Ψ Mass Shift and J∕Ψ-Nuclear Bound State

Abstract: Abstract. We calculate mass shift of the J/Ψ meson in nuclear matter arising from the modification of DD, DD * and D * D * meson loop contributions to the J/Ψ self-energy. The estimate includes the in-medium D and D * meson masses consistently. The J/Ψ mass shift (scalar potential) calculated is negative (attractive), and complementary to the attractive potential obtained from the QCD color van der Waals forces. Some results for the J/Ψ-nuclear bound state energies are also presented.Keywords: J/Ψ-nuclear boun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…with cutoff parameter Λ B [21][22][23][24][56][57][58][59][60], for each ΥBB vertex. In a later section we will discuss the nonneglegible role played by this form factor and the cutoff parameter Λ B .…”
Section: A υ Mass Shiftmentioning
confidence: 99%
“…with cutoff parameter Λ B [21][22][23][24][56][57][58][59][60], for each ΥBB vertex. In a later section we will discuss the nonneglegible role played by this form factor and the cutoff parameter Λ B .…”
Section: A υ Mass Shiftmentioning
confidence: 99%
“…Expanding this in terms of the components given in Eqs. (10) and (11), we obtain the following interaction Lagrangians [56],…”
Section: A Effective Lagrangians and υ Self-energymentioning
confidence: 99%
“…In the past few decades, many attempts were made [3][4][5][6] to find alternatives to the meson-exchange mechanism for the heavy-quarkonium-nucleon interaction. Some works employed charmed meson loops [7][8][9][10][11], others were based on QCD sum rules [12][13][14][15], phenomenological potentials [16,17], the charmonium color polarizability [18,19], and van der Waals type forces [7,[20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a lack of new experimental data of J/ψ production off a nucleon or nuclei near threshold a sustained theoretical activity on the subject ensued, over the past twenty years, for a better quantitative grasp of this color Van der Waals force. For example, Kaidalov and Volkovitsky [5] argued that S-wave quarkonia can be found in nuclei with A ≥10 with a binding energy of few MeV, de Teramond et al [6] in an update to his original paper with Brodsky [3] estimated a binding energy of 2 MeV in 12 C and 10 MeV in 208 Pb, while Shevchenko [7] pointed out in a later work that the interaction of charmonium-nucleon is so small that the potential depth for nuclear bound state may only exist for nuclei with A > 200. Applying QCD sum rules Hayashigaki [8] found a 4 to 7 MeV binding of the J/ψ in nuclear matter.…”
Section: Color Van Der Waals Forcesmentioning
confidence: 99%
“…Kawanai and Sasaki [10] calculated the charmonium-nucleon potential from the equal-time Bethe-Salpeter amplitude through the effective Schrödinger equation and found that the charmoniumnucleon potential is weakly attractive at short distances and exponentially screened at large distances. Tsushima, Lu, Krein and Thomas [11,12] have explored the ψ-nuclear bound states and found that the attractive potential that originates from the D and D * meson loops in the J/ψ in nuclear medium should produce bound states, they predicted binding energies from 5 MeV in 4 He to around 20 MeV in 208 Pb.…”
Section: Color Van Der Waals Forcesmentioning
confidence: 99%